A critical review on organic micropollutants contamination in wastewater and removal through carbon nanotubes. (15th September 2019) - Ahmad, Jahangir; Naeem, Shoaib; Ahmad, Munir; Usman, Adel R.A.; Al-Wabel, Mohammad I.
Abstract: The prevalence of organic micropollutants (OMPs) in various environmental compartments is posing a serious health risks to all kinds of lives on the planet. The levels of OMPs such as polyaromatic hydrocarbons, antibiotics, pesticides, contraceptive medicines, and personal care products in water bodies are increasing with each passing day. It is an urgent need of time to limit the release of OMPs into the environment, and to remove the prevailing OMPs for sustainable environmental management. The majority of the conventional means of water decontamination are either inefficient or expensive. However, due to nanosize, high surface area, and hollow and layered structure, carbon nanotubes (CNTs) serve as excellent sorbents for the removal of a diverse range of OMPs. The occurrence of emerging OMPs and their detrimental effects on human and animal health are collected and discussed in this review. The characteristics and efficacy of various CNTs (pristine and modified) for the efficient removal of different OMPs, and the removal mechanisms have been reviewed and discussed. The literature demonstrated that adsorption of OMPs onto CNTs is very complicated and rely on multiple factors including the properties of adsorbent and the adsorbate as well as solution chemistry. It was found that H–bonding, electrostatic interactions, van der Waals forces, hydrophobic interactions, H-π bongs, and π-π interactions were the major mechanisms responsible for the adsorption of OMPs onto various kinds of CNTs. Despite of higher affinities for OMPs, hydrophobicity and higher costs restrain the practical application of CNTs for wastewater treatment on large scale. However, continuous production may lead to the development of cost-effective, efficient and eco-friendly CTNs technology for wastewater treatments in future. Highlights: Prevalence, sources and health risks of emerging OMPs are discussed in this review. Functionalized CNTs could be used as an efficient technology for OMPs removal from wastewater. Hydrophobicity, impurity, and higher costs are major constraints for large scale applicability of CNTs. Continuous production may develop cost-effective and eco-friendly CTNs for wastewater treatments. Mechanism of OMPs adsorption onto CNTs is complicated and involves multiple factors.